What Determines Labour Force Participation of Tanzanian Women? - Mkenda, Beatrice (Tanzania Journal for Population studies and Development, 2014)
This paper estimates the determinants of labour force participation of Tanzanian women. It employs data from the 2006 Integrated Labour Force Survey. The key determinants found are: children (they both reduce and increase the odds of participation); age (it increases the odds of participation); marital status of women (it decreases and increases the odds of participation); education level (it increases the odds of participation); the education level of a woman’s spouse (it increases the odds of participation); the employment status of a woman’s spouse (it increases the odds of participation if spouses are in self-employment, but it reduces the odds of participation for other statuses); household income (higher incomes increase the odds of participation, but it reduces the odds of participation for women in lower incomes); and location (it increases the odds of participation for women living in urban areas but reduces the odds of participation for rural women). These findings have implications that can help to increase the participation of women in the labour force. Firstly, education (both for women and their spouses) remains a sure way of increasing the participation of women in the labour market by imparting and enhancing skills for more effective participation in the labour market. Secondly, child-minding programmes for women who are in their childbearing years are important so that having children does not constrain women’s participation in the labour force.